2006
DOI: 10.1007/s00405-006-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised controlled trial comparing Merocel and Rapid Rhino nasal tampons in the treatment of epistaxis

Abstract: A prospective study was performed to compare the efficacy and patient tolerance of Merocel and Rapid Rhino nasal tampons in the treatment of epistaxis. A total of 42 patients were studied. There was no significant difference between the two types of pack in efficacy or patient discomfort with pack in situ. Rapid Rhino produced significantly lower scores for subjective patient discomfort during insertion and removal of pack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 7 publications
1
54
1
Order By: Relevance
“…9, 10 Badran et al 7 studied 52 patients with epistaxis, and concluded that both pack types were equally effective in epistaxis control, but that Rapid Rhino packs were more comfortable for patients and easier for healthcare workers to insert and remove. Similar results were reported by Moumoulidis et al, 8 in their study of 42 patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…9, 10 Badran et al 7 studied 52 patients with epistaxis, and concluded that both pack types were equally effective in epistaxis control, but that Rapid Rhino packs were more comfortable for patients and easier for healthcare workers to insert and remove. Similar results were reported by Moumoulidis et al, 8 in their study of 42 patients.…”
Section: Discussionsupporting
confidence: 92%
“…Since the introduction of Rapid Rhino nasal packs, four clinical trials have compared them with Merocel nasal packs: two trails studied patients with epistaxis, 7,8 while the other two assessed pack use after nasal surgery. 9, 10 Badran et al 7 studied 52 patients with epistaxis, and concluded that both pack types were equally effective in epistaxis control, but that Rapid Rhino packs were more comfortable for patients and easier for healthcare workers to insert and remove.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely studied and compared with other packing materials and almost all investigations point to the fact that Merocel has a tendency to adhere to mucosa. Most importantly, Merocel causes more bleeding and discomfort during removal [2,3,12,13]. In our study, Merocel caused the highest pain scores during removal, whereas Merocel in the glove finger caused the least pain on removal, with the difference between these two treatments reaching statistical significance (p = 0.03).…”
Section: Discussioncontrasting
confidence: 41%
“…Most of the rhinologists are of the opinion that nasal packing is necessary as some bleeding after surgery is inevitable after meticulous surgery. 7 Though the measurement of pain is a complex problem with many pitfalls, the choice of visual analogue scale to measure pain as opposed to any other pain rating scales was based on the following advantages simplicity, high sensitivity and easily reproducible.…”
Section: Pain Score No Of Patients Minimum Score Maximum Score Meanmentioning
confidence: 99%